Hospital information systems and the factors influencing their implementation - Pilewski, Bartosz D.; Dżygadło, Barbara; Łepecka-Klusek, Celina (Nursing in the 21st Century, 2011)
Introduction. The development of medical sciences produces an ongoing increase of information about new diagnostic and therapeutic methods. Many of them undergo radical changes and storage of information and data processing within a short period of time causes many troubles. IT technology allows to control vast number of data and precise selection of “information hype” to diagnose, treat and manage health care settings efficiently. As an integral part of hospital structure hospital information system (HIS) is important for its two subsystems, i.e. medical service provided and administration. At the level of operating organization it is designed to provide basic data and answers to questions of routine procedures. At the managing level it aids administration to run monitoring and control. At the strategic level it facilitates the process of decision making as to trends and directions of future development. The main condition of successful implementation of information system into hospital setting is its personnel. If the goals of the project of HIS implementation are not accepted by hospital personnel, from hospital management to its basic line staff, the success is bound to fail. Aim. The purpose of the study was to present theoretical assumptions of HIS implementation into hospital setting and factors that condition the process.